On the role of monokines in the generation of nonspecific suppressor T cell activity in vitro - Baxevanis, C. N.; Dedousis, G. V.; Gritzapis, A. D.; Papadopoulos, N. G.; Arsenis, P.; Katsiyiannis, A.; Papamichail, M. (Immunopharmacol Immunotoxicol, 1994)
We examined the role of endogenously produced interleukin 1 beta (IL-1 beta) and tumor necrosis factor-alpha (TNF-alpha) in lectin-induced nonspecific suppressor activity in vitro. The cultures consisted of highly purified T lymphocytes, autologous monocytes and phytohemagglutinin (PHA). Kinetic studies revealed peak levels for both TNF-alpha and IL-1 beta production 4 hr after initiation of cultures which then declined and reached minimal levels on day 3. At this time point maximal levels of interleukin-2 (IL-2) were detected which declined sharply 24 hr later. The decline in cytokine levels in culture supernatants was most probably due to their consumption by the mononuclear cells which were found to express specific receptors for IL-1 beta, (IL-1 beta R), TNF-alpha (TNF-alpha R) and IL-2 (IL-2R) after 3- and 6-days of culture. After their first cycle of production and consumption both monokines were reproduced and the events followed the same patterns as for the first cycle: both monokines were first produced and at the time point of their consumption, IL-2 production reached maximal levels. The requirement for IL-1 beta and TNF-alpha in both IL-2 production and generation of suppressor activity was shown by three different approaches which included (a) blocking of HLA-DR molecules on monocytes which prevented monokine consumption during the early stages of culture, (b) blocking of HLA-A,B,C molecules on monocytes which prevented monokine consumption and IL-2 production late in culture, and (c) neutralization of monokine activity late in culture which resulted in highly reduced IL-2 production. T lymphocytes harvested from such cultures exhibited diminished suppressor activity. Our data suggest that the generation of nonspecific suppressor cell activity in vitro represents a complex system that requires cell interactions via self-major histocompatibility complex (MHC) antigen recognition and two cycles of cytokine production, where IL-1 beta and TNF-alpha production and consumption is a prerequisite for IL-2 production. Since lectin-induced nonspecific suppressor activity in vitro is deficient in certain autoimmune disorders the data presented herein might help in understanding the cellular basis for this immunodeficiency.
Keywords: Antibodies; Cultured HLA Antigens Humans Interleukin-1 Interleukin-2 Monokines Phytohemagglutinins Receptors; Interleukin-2 T-Lymphocyte Subsets T-Lymphocytes; Monoclonal Cells; Regulatory Tumor Necrosis Factor-alpha